ANALISIS RESPON DAN KEAKTIFAN MAHASISWA TERHADAP PEMBELAJARAN DARING MENGGUNAKAN ZOOM - Kurnia, Ulfa Isni; Alfina; Kurniawansah, Alfi; Lusi Novita Batubara, Sandra; Setiawan, Susilo; HS, Asril (Jurnal Pendidikan Teknologi Informasi (J-Diteksi), 2023)
Analysis of student response and activity in daring learning using zoom aims to see and describe the process of daring learning , so an analysis of student responses and activeness is needed during the brave learning process so that learning objectives are met even though the learning process is not carried out directly or face to face. The research method used is a type of qualitative research with a phenomenological approach. The subjects used were Information Technology Education students at Aisyah Pringsewu University. Data collection techniques used are interviews, observations and field notes. Research is done boldly. The data analysis technique uses the Miles & Huberman model which consists of three stages, namely data reduction, data display, and verification. The results of the study show that the zoom application can support the learning process of challenges, students respond well during the learning process of challenges but sometimes there are problems with the signal/network, and students are active during the learning process by conducting questions and answers during discussions.